The Relationship between Heart Rate Variability and Heart Rate Turbulence Dynamics after Primary Coronary Angioplasty - Kurpesa, Małgorzata (Ann Noninvasive Electrocardiol, 2007)
Background: The application of heart rate turbulence (HRT) analysis for risk assessment after pharmacologically treated myocardial infarction (MI) was described in 1999. The aim of the present study was to evaluate the dynamics of HRT changes in long‐term observation after MI treated with primary coronary angioplasty (PTCA). Moreover, the usefulness was assessed of early postinfarction heart rate variability (HRV) analysis for predicting HRT dynamics. Methods: The study group consisted of 96 patients with MI treated with primary PTCA. Holter monitoring with HRV and HRT analysis was performed 3 days after the procedure and 1 year later. Results: Twelve months after primary PTCA, an improvement (Type I HRT dynamics) was noted in 51 patients, and the worsening of both the HRT parameters (Type II HRT dynamics) in 34 patients. Fourteen patients showed the worsening of only one HRT parameter (Type III HRT dynamics). The following HRV parameters recorded in early postinfarction Holter monitoring had a significant influence on the risk of Type II HRT dynamics: SDNN, RMSSD, Triangle Index and Δ LF/HF (mean day‐time LF/HF – mean night‐time LF/HF). Only the latter was found in the multivariate analysis as significantly connected with worsened HRT. During the follow‐up, SDNN and Triangular Index improved in all the patients. Conclusions: HRT after myocardial infarction treated with primary PTCA presents a significant dynamics, which is different than dynamics of HRV. An abnormal circadian pattern of autonomic activity is a finding that helps identify patients who need to have HRT analysis repeated during a long‐term follow‐up, due to the tendency for HRT to change with time toward the prognostically unfavorable values.